Assessment of hybrid alkali-activated fly ash–limestone powder as sustainable rendering mortar - Todsaporn Srikhamma; Chattarika Phiangphimai; Tanakorn Phoo-ngernkham; Satakhun Detphan; Sakonwan Hanjitsuwan; Kosawat Changjatturas; Nattavude Kongmuang; Prinya Chindaprasirt (Case Studies in Construction Materials)
This study evaluates the potential of a hybrid alkali-activated material (HAAM) mortar, formulated using high-calcium fly ash (FA) and limestone powder (LP), as a sustainable and economically viable alternative to conventional rendering mortars. Two HAAM mortar formulations were investigated, with 0 wt% and 50 wt% LP replacement of FA, using a constant sand-to-binder ratio of 2.0 and a 6-molar sodium hydroxide solution as an activator. A comprehensive experimental program assessed setting time, compressive strength, water retention, air content, and bond strength via pull-off tests, complemented by a cost analysis and life-cycle assessment. Test results indicated that FA-based HAAM mortars incorporating LP achieved acceptable performance, meeting ASTM and TIS requirements for masonry applications. The inclusion of LP reduced setting time and improved early compressive strength. Furthermore, water retention and air content in the FA-LP-based HAAM mortar were comparable to those of the commercial mortar. Bond strength was enhanced in all brick types, particularly cement bricks, due to the formation of additional reaction products at the interface. Although the FA-LP-based HAAM mortar had a higher initial cost than the control, it proved more cost-effective in the long term and exhibited a lower carbon footprint. These findings highlight the potential of FA-LP-based HAAMs as environmentally friendly rendering mortars for masonry applications, offering improved sustainability and economic efficiency.